Arene–Ruthenium(II) Complexes with Bioactive ortho‐Hydroxydibenzoylmethane Ligands: Synthesis, Structure, and Cytotoxicity. Issue 12 (19th December 2016) - Pettinari, Riccardo; Petrini, Agnese; Marchetti, Fabio; Pettinari, Claudio; Riedel, Tina; Therrien, Bruno; Dyson, Paul J.
Abstract : The synthesis of a series of neutral arene–ruthenium(II) complexes (arene = p ‐cymene, hexamethylbenzene, and benzene) [(arene)Ru(HDB)Cl] derived from the reaction of the appropriate arene–ruthenium(II) dimers and ortho ‐hydroxydibenzoylmethane (HDBH), a potent inhibitor of cell proliferation, is described. In addition, related ionic complexes [(arene)Ru(HDB)(PTA)](SO3 CF3 ) (PTA = 1, 3, 5‐triaza‐7‐phosphaadamantane) have been prepared. The structure of three complexes has been confirmed by X‐ray crystallography. The cytotoxicity of the complexes has been evaluated against human ovarian carcinoma cells (A2780 and A2780cisR), as well as against nontumorigenic human embryonic kidney (HEK293) cells, and compared to the free ligand and cisplatin. Two of the complexes, that is from the first series with p ‐cymene and hexamethylbenzene, display relevant activities against the cisplatin‐resistant A2780cisR cancer cell line. Abstract : Arene–Ru II complexes of ortho ‐hydroxydibenzoylmethane show an intramolecular H bond in both the solid state and solution. They display good cytotoxicity in vitro against human ovarian carcinoma A2780 and even superior activity against A2780cisR cells.